Efecto de las prácticas de rehabilitación: podas y raleos en el desempeño productivo de plantaciones de cacao (Theobroma cacao L.) en el Ecuador - Gurumendi Monserrate, Paulina Alejandra (2025)
At a global level, cocoa has been a product of greater consumption that is increasingly representing the strengthening of the value chain. Ecuador, due to its biological wealth, is a cocoa producer par excellence, being one of the main export products. The main objective of the research was to study the effect of rehabilitation practices: pruning and thinning on the productive performance of cocoa plantations (Theobroma cacao L.). For the preparation of the document, information was collected from scientific articles and libraries, presenting it as a non-experimental research of a bibliographic nature. The results indicate that rehabilitation in cocoa cultivation is essential for the restoration of trees and optimizing the performance of plantations. This includes pruning, integrated management of pests and diseases, and adoption of optimal agricultural practices. Adequate pruning and thinning generates benefits such as pest mitigation, growth stimulation, and maintenance of shade. The conclusions indicate that the rehabilitation of cocoa plantations is essential to revitalize trees, help with integrated management of pests and diseases, and adopt good agricultural practices, which favors the sustainability of these crops. The essential pruning methods are: training, which establishes the structure of the tree; maintenance, which removes dead branches; rehabilitation, which removes aged foliage; and renewal, which regenerates plants that have reached an aging state. These agronomic benefits include a decrease in the incidence of pests and diseases, an increase in fruit production, and maintenance of shade.